2014
DOI: 10.1155/2014/756975
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Use of MicroRNAs in Lung Cancer

Abstract: Lung cancer is a leading cause of cancer deaths worldwide. Although the molecular pathways of lung cancer have been partly known, the high mortality rate is not markedly changed. MicroRNAs (miRNAs) are small noncoding RNAs that actively modulate cell physiological processes as apoptosis, cell-cycle control, cell proliferation, DNA repair, and metabolism. Several studies demonstrated that miRNAs are involved in the pathogenesis of lung diseases including lung cancer and they negatively regulate gene and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 94 publications
0
29
0
Order By: Relevance
“…Recent studies have focused on aberrant expression of the let-7 and miR-34 families in lung tumour tissues when compared to the normal lung tissue, which can indicate the involvement of those miRNAs in lung carcinogenesis [169].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Recent studies have focused on aberrant expression of the let-7 and miR-34 families in lung tumour tissues when compared to the normal lung tissue, which can indicate the involvement of those miRNAs in lung carcinogenesis [169].…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Deregulation of miRNAs has been observed in a wide range of human diseases, including HCC or other cancers . Our previous study identified several deregulated miRNAs in HCC tumor tissues (data not shown), of which miR‐199a‐5p was the most significance (Fold change: 0.0023, p <0.001).…”
Section: Introductionmentioning
confidence: 89%
“…9 Deregulation of miRNAs has been observed in a wide range of human diseases, including HCC or other cancers. [10][11][12][13][14][15] Our previous study identified several deregulated miRNAs in HCC tumor tissues (data not shown), of which miR-199a-5p was the most significance (Fold change: 0.0023, p<0.001). Although down-regulation of miR-199a-5p has been reported by others, the roles of miR-199a-5p and its novel targets are still worthy to be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Antagomirs (synthetic analogues of miRNA) can induce a specific and long-lasting silencing of miRNAs and thereby can control gene expression [142]. Delivery of miRNAs as synthetic miRNA mimics or antagomirs has emerged as a promising approach to treat lung cancer, and this topic has been recently reviewed [143]. Among the different non-viral nanosized systems used to deliver miRNAs to the lung were solid lipid nanoparticles (SLNs) containing dimethyldioctadecylammonium bromide (DDAB) [144], liposomal formulations containing either DOTMA [145] or NOV340/miR-200c (SMARTICLES; a proprietary liposomal formulation containing amphoteric lipids that are cationic at low pH and neutral or anionic at neutral and higher pH) [146].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%